Time Series Implementation for Sales Forecasting of Furniture Products at PT XYZ - Pramastya, Pragnanta Yopie; Mailoa, Evangs (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
PT XYZ is an importer, distributor, and seller of furniture. The company operates in two business lines: B2B (Business to Business) and B2C (Business to Consumer). The B2B segment is divided into Agents/Local Distributors, Modern Trade, and Partner Retail Stores, while the B2C segment is divided into Direct Sales and Online Intermediaries. This study applies the Time Series method to forecast future furniture sales using the SARIMA (Seasonal Autoregressive Integrated Moving Average) model. The results of the study using the SARIMA model provide sales forecasts from 2024 to 2026.